Inguinal hernia repair – TEP or TAPP?? A comparative analysis between both the laparoscopic procedures in a tertiary care center - Rab, Atia Zaka Ur; Alim, Sheikh Saif; Ali, Wasif Mohammad; Ali Rizvi, Syed Amjad (Asian Journal of Medical Sciences, 2020)
Background: Inguinal hernia surgery is one of the most common elective procedures performed by the surgeons and has evolved from open to the laparoscopic technique. Aims and Objectives: This prospective study was conducted to find out intra-operative and post-operative outcomes in patients undergoing TEP and TAPP for inguinal hernia repair. Materials and Methods: A prospective study was conducted on 50 adult patients who underwent laparoscopic inguinal hernia repair between November 2017 to November 2018. It was a randomized study and equal number of patients were allocated to TAPP and TEP group based on the surgeon’s preference. Results: Operative time [p<0.0001], intensity of pain (VAS) was significantly higher in TAPP compared to TEP in the immediate post-operative period (6 hours) and during hospital stay [p=0.0299]. No significant difference observed in VAS between TEP and TAPP during follow up [after 1 week (p=0.2298), 2 weeks (p=0.2337), and 4 weeks (p=0.3944)]. Both TEP and TAPP were comparable in terms of Intra-operative and Post-operative complications seroma [during hospital stay (p=0.1573), after 1 week (p=0.6375), after 2 weeks (p=0.5513)]; haematoma [during hospital stay (p=0.1492), after 1 week (p=0.3125)] and Conversion (p=0.3125), and Length of hospital stay (p=0.3960). Time to resume normal work [p<0.0001] was significantly more in TAPP than TEP. Conclusion: TEP has a definite edge over TAPP taking into consideration the lesser intensity of post-operative pain during hospital stay, shorter duration of surgery and relatively early return to normal work associated with the former procedure. TEP should therefore be regarded as the procedure of choice for inguinal hernia repair.